(3ChVM GdeSGdc Edi CdajI GHf eGdcs - (3GHf gTGe, CHh eMeO, LeGd GdOjf, GHf gTGe, YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg, J (B761(3g` (B1360(3es
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO MeO Gddg eSJMb GdMeO (B... (3gPG HGH TQM GdcdGe hTQM eG jJCda GdcdGe efg, GdcdGe aj GUWdGM GdfMhjjf YHGQI YeG GLJeY ajg CeQGf GddaX hGdEaGOIs
(3BNQgG (B:s
(3BNQgG(B: (3hEPG Scf GdMQa GdeOZe ajg dGJUGdg HVejQ GdQaY hLH ac GdEOZGe aj dZI ZjQ HcQ Hf hGFd fMh MccJ hbd Ef VddJ hTOOfG CSQge, hbO jac GdEOZGe aj ZjQ Pdc TP fMh dMMJ Yjfg (B... (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 147s
(3cTa GdXfhf, L (B1: 152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs